Los inicios de la expansión ibérica en el Atlántico y el Imperio alemán. Un aporte historiográfico - Pietschmann, Horst (Revista Complutense de Historia de América, 2006)
The contribution deals with an innovative area of the americanist research. It attends to the limits and progress of german historiography concerning the iberian atlantic expansion. It focusses on the most important authors that have approached to the subject from the XV century up to nowadays, to reveal the links between the german Empire and the iberian Peninsula in items such as travels, society, economy and culture.